2008
DOI: 10.1063/1.2827584
|View full text |Cite
|
Sign up to set email alerts
|

Effective velocity for transport in heterogeneous compressible flows with mean drift

Abstract: Solving transport equations in heterogeneous flows might give rise to scale dependent transport behavior with effective large scale transport parameters differing from those found on smaller scales. For incompressible velocity fields, homogenization methods have proven to be powerful in describing the effective transport parameters. In this paper, we aim at studying the effective drift of transport problems in heterogeneous compressible flows. Such a study was done by Vergassola and Avellaneda in Physica D 106… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…One of the challenges is the observation of drift phenomena at a Darcy or field scale [5,16]. The signatures of drift phenomena affect tracer concentration distribution at field scale as reported in the literature [22]. Analytical model solutions that describe and predict tracer transports at field scale have been obtained in cases where tracer adsorption, non-uniform convection, and variable dispersion manifest [23].…”
Section: Pore-scale Radial Diffusion Models With Driftmentioning
confidence: 99%
“…One of the challenges is the observation of drift phenomena at a Darcy or field scale [5,16]. The signatures of drift phenomena affect tracer concentration distribution at field scale as reported in the literature [22]. Analytical model solutions that describe and predict tracer transports at field scale have been obtained in cases where tracer adsorption, non-uniform convection, and variable dispersion manifest [23].…”
Section: Pore-scale Radial Diffusion Models With Driftmentioning
confidence: 99%
“…Attinger and Abdulle [15] studied the effective drift of transport problems in heterogeneous compressible flows. They discussed the impact of a mean drift and showed that static compressible flow with mean drift can produce a heterogeneity-driven large-scale drift or ballistic transport.…”
Section: Introductionmentioning
confidence: 99%